Fichte’s Proposition «I am» - Stolzenberg, Jürgen (Sententiae, 2014)
The paper deals with Johann Gottlieb Fichte’s argument in § 1 of the «Foundations of the Science of Knowledge» (1794). Reconstructing the crucial argument of the § 1 of «Foundations…» step by step, the author shows how Fichte infers the proposition «I am» from the log-ical proposition of identity «A is A». In doing so, the author claims that proposition «I am», which expresses what Fichte calls «Tathandlung», has to be understood as a critical response to Carl Leonhard Reinhold’s methodological program which emphasizes the starting point of philosophy as a «fact of consciousness». Furthermore, the paper shows the difference between Fichte’s argument of the § 1 of «Foundations…» and his first attempt of its application in the «Private Meditations on Elementary Philosophy» (1793/94) which deals with the concept of an intellectual intuition of the «I» and which in turn can be understood as referring to a fact of consciousness. Therefore, Fichte’s argument leading to the proposition «I am» in the § 1 of «Foundations…», is the result of a self-critical revision of his very first conception of the «I».